2017
DOI: 10.1007/s12192-017-0766-0
|View full text |Cite
|
Sign up to set email alerts
|

The six Tomato yellow leaf curl virus genes expressed individually in tomato induce different levels of plant stress response attenuation

Abstract: Tomato yellow leaf curl virus (TYLCV) is a begomovirus infecting tomato plants worldwide. TYLCV needs a healthy host environment to ensure a successful infection cycle for long periods. Hence, TYLCV restrains its destructive effect and induces neither a hypersensitive response nor cell death in infected tomatoes. On the contrary, TYLCV counteracts cell death induced by other factors, such as inactivation of HSP90 functionality. Suppression of plant death is associated with the inhibition of the ubiquitin 26S p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Silencing of HSP70 in the tomato plant controlled the viral infection. Conversely, HSP90 knockdown promoted viral infection [10,111]. A recent study on Potato Virus Y (PVY) in potato thermo-tolerant and sensitive genotypes under heat stress, HSPs was induced in both genotypes.…”
Section: Role Of Hsps In Plant Defensementioning
confidence: 99%
See 1 more Smart Citation
“…Silencing of HSP70 in the tomato plant controlled the viral infection. Conversely, HSP90 knockdown promoted viral infection [10,111]. A recent study on Potato Virus Y (PVY) in potato thermo-tolerant and sensitive genotypes under heat stress, HSPs was induced in both genotypes.…”
Section: Role Of Hsps In Plant Defensementioning
confidence: 99%
“…Plants continuously confront harsh environments like high/low temperatures, drought, salts, heavy metals, light, flooding and physical wounding [2,3,4,5]. Biotic stresses like pathogens (Viruses, Bacteria, Fungi) and pests such as nematodes, insects, and rodents also restrict plant productivity [6,7,8,9,10]. Negative effects of these stresses on the plant germination [11], are stunted growth [12,13], sunburn and scorching of leaves [14], loss of photosynthetic pigment, decreased production of photo-assimilates, and depletion of carbohydrate reserves which results in starvation [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, V2 is shown to affect host cell death by interacting with and inhibiting enzymatic activity of CYP1, a plant programmed cell death machinery component [11]. A recent report showed that overexpression of V2 induced cell death symptoms in tomato, in contrast to no cell death caused by TYLCV infection [12]. But a healthy environment ensures the survival and multiplication of TYLCV, so the accumulation of TYLCV was hindered at the late stages of infection [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report showed that overexpression of V2 induced cell death symptoms in tomato, in contrast to no cell death caused by TYLCV infection [12]. But a healthy environment ensures the survival and multiplication of TYLCV, so the accumulation of TYLCV was hindered at the late stages of infection [12]. These results suggest that the individual viral proteins are insufficient to account for the TYLCV disease symptoms and other viral factor(s) may also contribute to the pathogenesis of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate sweet potato's defense response against SPVD and to discover potential SPVD resistance mechanisms, we explored DEGs related to plant-pathogen interaction and defense response. Homologs of heat shock protein 70 (HSP70) and heat shock protein 90 (HSP90) genes, which have been reported to play key roles in resistance to viruses in plants [23][24][25], were significantly induced in SPFMV and SPCSV-infected sweet potato. The RPM1-interacting protein 4 (RIN4) gene homolog was also upregulated, as were unigenes encoding WRKY1, WRKY6, WRKY22, and WRKY40-like WRKY transcriptional factors.…”
Section: Degs That Participate In the Response To Spvdmentioning
confidence: 99%